2008
DOI: 10.1093/sleep/31.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in Sympathetic and Vagal Activities During Sleep-Wake Transitions

Abstract: The parasympathetic activity before falling asleep and the sympathetic activity before waking up change coincidentally with EEG frequency, and may respectively contain the messages of sleeping and waking drives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 24 publications
(28 reference statements)
4
42
1
1
Order By: Relevance
“…It has been reported that parasympathetic activity has an active role involved in the transition from awake to sleep in rats. (40) In a human study, insomnious patients presented with a higher sympathovagal balance compared to normal subjects both before and after sleep onset. (41) These results seem to help explain why the deficiency-yang pattern individuals had difficulty falling asleep and subsequently had lower sleep effi ciency than the defi ciency-yin pattern individuals.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that parasympathetic activity has an active role involved in the transition from awake to sleep in rats. (40) In a human study, insomnious patients presented with a higher sympathovagal balance compared to normal subjects both before and after sleep onset. (41) These results seem to help explain why the deficiency-yang pattern individuals had difficulty falling asleep and subsequently had lower sleep effi ciency than the defi ciency-yin pattern individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Animals that received a single intraplantar CFA injection underwent behavioral tests after 4,8,12,16,20, and 24 h. The baseline median PWT in NN rats was significantly higher than in CON rats ( p = 0.001; Fig. 1 ).…”
Section: Hyposensitivity At Baseline and Evoked Mechanical Pain Hypermentioning
confidence: 94%
“…1 ). Injection of CFA caused a significant reduction in PWT at every time point ( p < 0.001, respectively, for 4,8,12,16,20, and 24 h vs. baseline), both in CON and NN rats (not labeled). The median PWT in NN rats was significantly lower at 16,20, and 24 h when compared with CON rats ( p < 0.007 after a Bonferroni adjustment; Fig.…”
Section: Hyposensitivity At Baseline and Evoked Mechanical Pain Hypermentioning
confidence: 97%
See 1 more Smart Citation
“…El CSV es el mayor modulador de la actividad autonómica; a modo de ejemplo, el SNREM se asocia con una disminución del SNS y un incremento del tono SNPS respecto de la vigilia 77 , cambios que se revierten parcialmente durante el SREM 78 . En este sentido los cambios en la cantidad o calidad del sueño podrían manifestarse en modifi caciones de la regulación del SNA.…”
Section: C) Regulación Del Snaunclassified